Doppler ultrasonographic evaluation of splanchnic blood flow in coeliac disease. Issue 3 (September 1996) - Arienti, V; Califano, C; Brusco, G; Boriani, L; Biagi, F; Giulia Sama, M; Sottili, S; Domanico, A; Corazza, G R; Gasbarrini, G
Abstract : BACKGROUND: Current knowledge on splanchnic haemodynamics in coeliac disease is limited and incomplete. AIM: To evaluate splanchnic arterial and venous blood flow in coeliac disease. METHODS: In 22 coeliac (13 untreated, nine treated) patients and in nine healthy subjects the following variables were assessed: vessel diameter and mean flow velocity in portal vein, splenic vein, superior mesenteric vein, and superior mesenteric artery. Peak systolic velocity, end diastolic velocity and pulsatility index were also determined in the superior mesenteric artery. Five patients of the untreated group were re-evaluated after nine months on a gluten free diet. RESULTS: Significant differences in haemodynamic variables between the three groups were shown only in the superior mesenteric artery. An increase in both mean flow velocity and end diastolic velocity and a reduction in pulsatility index occurred in untreated patients compared with treated patients (p < 0.002; p < 0.04; p < 0.035) and with healthy controls (p < 0.001; p < 0.025; p < 0.0003). Similar results were obtained for the five patients evaluated before and after treatment (p < 0.03; p < 0.02; p < 0.03), in whom the mean flow velocity in the superior mesenteric vein also decreased after treatment (p < 0.05). No significant differences were noted between treated coeliac patients and healthy controls. CONCLUSIONS: In untreated coeliac disease there is a hyperdynamic mesenteric circulation that decreases after treatment.